Influence of Micropore and Mesoporous in Activated Carbon Air-cathode Catalysts on Oxygen Reduction Reaction in Microbial Fuel Cells. (1st October 2016) - Liu, Yi; Li, Kexun; Ge, Baochao; Pu, Liangtao; Liu, Ziqi
Graphical abstract: Abstract: In this study, carbon samples with different micropore and mesoporous structures are prepared as air-cathode catalyst layer to explore the role of pore structure on oxygen reduction reaction. The results of linear sweep voltammetry and power density show that the commercially-produced activated carbon (CAC) has the best electrochemical performance, and carbon samples with only micropore or mesoporous show lower performance than CAC. Nitrogen adsorption-desorption isotherms analysis confirm that CAC has highest surface area (1616 m 2 g −1 ) and a certain amount of micropore and mesoporous. According to Tafel plot and rotating disk electrode, CAC behaves the highest kinetic activity and electron transfer number, leading to the improvement of oxygen reduction reaction. The air permeability test proves that mesoporous structure enhance oxygen permeation. Carbon materials are also analyzed by In situ Fourier Transform Infrared Spectroscopy and H2 temperature programmed reduction, which indicate that micropore provide active sites for catalysis. In a word, micropore and mesoporous together would improve the electrochemical performance of carbon materials.